2015
DOI: 10.3944/aott.2015.14.0108
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pathological fractures due to simple bone cysts by extended curettage-grafting and intramedullary decompression

Abstract: Complete cyst healing and satisfactory functional results can be obtained by curettage grafting and intramedullary decompression. This technique restores bone integrity by allowing early motion and prevents refracture and subsequent deformity in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
14
0
2
Order By: Relevance
“…Erol et al reported a comparative study for the treatment of simple bone cysts of the humerus, which suggested that although perfect functional results were possible with open curettage and grafting, continuous intramedullary decompression with elastic nails led to a higher radiographic healing rate [34]. Meanwhile, Erol's group also proved that, the treatment with intramedullary nail was able to support the restore of bone integrity by allowing early motion as well as preventing refracture and subsequent deformity in the majority of patients [19]. Percutaneous and less invasive methods are widely promoted because of the advantages of lower infection rates, fewer wound problems, smaller scars, less anesthetic and fewer complications, making it easier for patients and their families to accept a surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erol et al reported a comparative study for the treatment of simple bone cysts of the humerus, which suggested that although perfect functional results were possible with open curettage and grafting, continuous intramedullary decompression with elastic nails led to a higher radiographic healing rate [34]. Meanwhile, Erol's group also proved that, the treatment with intramedullary nail was able to support the restore of bone integrity by allowing early motion as well as preventing refracture and subsequent deformity in the majority of patients [19]. Percutaneous and less invasive methods are widely promoted because of the advantages of lower infection rates, fewer wound problems, smaller scars, less anesthetic and fewer complications, making it easier for patients and their families to accept a surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, new treatments have been developed, such as intralesional injections of steroids [13,14], intralesional injections of bone marrow [15], bone grafting with homologous cancellous bone chips [16], bone grafting with freeze-dried crushed cortical bone [17], and decompression with screws or pins with holes [18]. Even though these new surgical treatments present promising short-term outcomes, most of them are likely to end up with partial recoveries [19], and the recrudesce and tenacity are still the biggest challenges [3].…”
Section: Introductionmentioning
confidence: 99%
“…Os cistos ósseos simples foram descritos pela primeira vez por Virchow em 1876. 10 A maioria dos cistos ósseos simples é observada na infância e definida como uma lesão do desenvolvimento/reativa. Sua etiologia é desconhecida.…”
Section: Discussionunclassified
“…Injeções locais de corticosteroides, transplante autólogo de medula óssea ou injeções de matriz óssea desmineralizada, autoaloenxertos de osso cortical-esponjoso, e muitos outros procedimentos foram descritos na literatura. 6,7,10 Não existem princípios definidos sobre a forma de tratamento dos cistos ósseos simples, e cada método terapêutico apresenta taxas de sucesso e complicações específicas. 11 Em nosso caso, as indicações para a cirurgia foram os achados radiográficos condizentes com lesão cística no acrômio, e o histórico clínico relacionado à lesão.…”
Section: Discussionunclassified
“…In recent decades, new treatments have been developed, such as intralesional injections of steroids [13], intralesional injections of bone marrow [14], bone grafting with homologous cancellous bone chips [15], bone grafting with freeze-dried crushed cortical bone [16], and decompression with multiple drill holes [17]. Even though these new surgical treatments present promising short-term outcomes, most of them are likely to end up with partial recoveries [18], and the recrudesce and tenacity are still the biggest challenges [3].…”
Section: Introductionmentioning
confidence: 99%